The trithorax group gene moira encodes a brahma-associated putative chromatin-remodeling factor in Drosophila melanogaster. - Crosby, M.A.; Miller, C.; Alon, T.; Watson, K.L.; Verrijzer, C.P.; Goldman-Levi, R.; Zak, N.B. (Molecular and Cellular Biology, 1999)
The genes of the trithorax group (trxG) in Drosophila melanogaster are required to maintain the pattern of homeotic gene expression that is established early in embryogenesis by the transient expression of the segmentation genes. The precise role of each of the diverse trxG members and the functional relationships among them are not well understood. Here, we report on the isolation of the trxG gene moira (mor) and its molecular characterization. mor encodes a fruit fly homolog of the human and yeast chromatin-remodeling factors BAF170, BAF155, and SWI3. mor is widely expressed throughout development, and its 170-kDa protein product is present in many embryonic tissues. In vitro, MOR can bind to itself and it interacts with Brahma (BRM), an SWI2-SNF2 homolog, with which it is associated in embryonic nuclear extracts. The leucine zipper motif of MOR is likely to participate in self-oligomerization; the equally conserved SANT domain, for which no function is known, may be required for optimal binding to BRM. MOR thus joins BRM and Snf5-related 1 (SNR1), two known Drosophila SWI-SNF subunits that act as positive regulators of the homeotic genes. These observations provide a molecular explanation for the phenotypic and genetic relationships among several of the trxG genes by suggesting that they encode evolutionarily conserved components of a chromatin-remodeling complex.